Abrasive Waterjet (AWJ) Forces-Potential Indicators of Machining Quality - Hlaváč, Libor M; Annoni, Massimiliano P G; Hlaváčová, Irena M; Arleo, Francesco; Viganò, Francesco; Štefek, Adam (Materials (Basel, Switzerland), 2021)
The necessity of monitoring the abrasive waterjet (AWJ) processes increases with the spreading of this tool into the machining processes. The forces produced on the workpiece during the abrasive waterjet machining can yield some valuable information. Therefore, a special waterjet-force measuring device designed and produced in the past has been used for the presented research. It was tested during the AWJ cutting processes, because they are the most common and the best described up-to-date AWJ applications. Deep studies of both the cutting process and the respective force signals led to the decision that the most appropriate indication factor is the tangential-to-normal force ratio (TNR). Three theorems concerning the TNR were formulated and investigated. The first theorem states that the TNR strongly depends on the actual-to-limit traverse speed ratio. The second theorem claims that the TNR relates to the cutting-to-deformation wear ratio inside the kerf. The third theorem states that the TNR value changes when the cutting head and the respective jet axis are tilted so that a part of the jet velocity vector projects into the traverse speed direction. It is assumed that the cutting-to-deformation wear ratio increases in a certain range of tilting angles of the cutting head. This theorem is supported by measured data and can be utilized in practice for the development of a new method for the monitoring of the abrasive waterjet cutting operations. Comparing the tilted and the non-tilted jet, we detected the increase of the TNR average value from 1.28 ± 0.16 (determined for the declination angle 20° and the respective tilting angle 10°) up to 2.02 ± 0.25 (for the declination angle 30° and the respective tilting angle of 15°). This finding supports the previously predicted and published assumptions that the tilting of the cutting head enables an increase of the cutting wear mode inside the forming kerf, making the process more efficient.
Keywords: normal force; abrasive waterjet; deformation wear; tangential force; kerf characteristics; cutting wear